2001
DOI: 10.1007/s000110050719
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induces apoptosis of chondrocytes; involvement of calcium ion and extracellular signal-regulated protein kinase

Abstract: Hydrogen peroxide induces chondrocyte apoptosis via Ca2+ signaling, and ERK is involved in these signal transduction pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 25 publications
5
69
0
Order By: Relevance
“…Results of our study demonstrated that, contrary to previous studies, H 2 O 2 may not induce chondrocyte apoptosis through caspase activation. 10,11 The secondary aim of the study was to evaluate the putative protective effect(s) of HPL extract against H 2 O 2 -induced alterations in apoptosis rate as well as the differences in aggrecan degradation in OUMS-27 cells using a viability test, comet assay, Caspase-1, and ADAMTS enzymes. Chondrocytes were pretreated with HPL extract and incubated with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Results of our study demonstrated that, contrary to previous studies, H 2 O 2 may not induce chondrocyte apoptosis through caspase activation. 10,11 The secondary aim of the study was to evaluate the putative protective effect(s) of HPL extract against H 2 O 2 -induced alterations in apoptosis rate as well as the differences in aggrecan degradation in OUMS-27 cells using a viability test, comet assay, Caspase-1, and ADAMTS enzymes. Chondrocytes were pretreated with HPL extract and incubated with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS production is considered to be an important cause of chondrocyte dysfunction and articular cartilage degradation, which leads to the pathogenesis of OA and the aging of cartilage (7)(8)(9)(10). Chondrocytes and cartilage tissues exhibit efficient protective strategies to minimize damage induced by increased ROS production, including H 2 O 2 (7,11). Previous studies have investigated various antioxidant supplements, including resveratrol, quercetin, vitamin E, and other strategies (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators in our group have previously demonstrated that ROS are involved in cartilage degradation associated with inflammatory joint disease (1)(2)(3)(4).…”
mentioning
confidence: 99%